Strengthening Participation through Public Policy Networks for Village Financial Accountability - Abi Ibnu Majid; N. Ngadisah; R. Rulinawaty (Golden Ratio of Social Science and Education, 2026)
This study aims to analyze actor participation in the public policy network of village financial management in Lebao Village, East Solor District, East Flores Regency. This study focuses on three research questions: (1) the level of actor participation in the public policy network of village financial management, (2) the factors influencing actor participation, and (3) the mechanisms for strengthening participation within the public policy network of village financial management. This study employed a qualitative approach with a case study design. Data collection techniques included in-depth interviews, direct non-participation of observation, and documentation, which were subsequently analyzed using the interactive analysis model of Miles and Huberman. The study involves four key informants selected through purposive sampling: the Village Head, members of the Village Consultative Body (BPD), a neighborhood head (RT), and a female representative. The results indicate that actor participation in the public policy network of village financial management in Lebao Village is formally high through village deliberation forums. However, participation remains influenced by the dominance of key actors, particularly the village government and the BPD. Factors affecting participation include individual motivation, community literacy capacity, information transparency, leadership style, and power structure within the policy network. Mechanisms for strengthening participation are carried out through active community involvement in deliberation forums, transparent information dissemination, capacity building, and implementing open evaluation forums. The main challenges identified are the limited availability of public information media and the suboptimal involvement of external actors in the policy network